Top 10 Raptors of Northern Belize - Elizabeth Scarlett; Venetia Briggs-Gonzalez; Justin Dalaba; Jorge E. Ruano; Frank Mazzotti (EDIS)
More than 500 species of birds visit or live in Belize and because of its location, Northern Belize serves as an important stop-over point and attracts a large majority of migratory birds in addition to its year-round residents. This guide showcases the top 10 raptor species (predatory birds) that you are most likely to encounter while in Northern Belize.